PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP MASYARAKAT DALAM MENCEGAH PENYAKIT DIABETES TIPE 2 DI DESA KENANGAN BARU - Doris Norintan Sinaga; Lenny Lusia Simatupang (Indonesian Trust Nursing Journal, 2026)
Diabetes mellitus is a non-communicable disease whose prevalence continues to increase and becomes a public health problem. Lack of knowledge and inappropriate attitudes towards a healthy lifestyle are risk factors for the increasing incidence of type 2 diabetes. Preventive efforts can be carried out through health education to increase knowledge and shape positive attitudes in the community. Objective of this study is to analyze the effect of healthy lifestyle health education on community knowledge and attitudes in preventing type 2 diabetes in Kenangan Baru Village. This type of research is a quantitative study with a quasi-experimental research design with a one group pretest-posttest approach. The sample in this study amounted to 50 respondents selected using a purposive sampling technique. The instrument used was a knowledge and attitude questionnaire. Data analysis was carried out using the Paired Sample T-Test and the Wilcoxon test. The results of the study showed an increase in the average score of knowledge and attitudes after being given health education. The statistical test results showed a p-value <0.05, indicating a significant effect of healthy lifestyle health education on improving public knowledge and attitudes regarding type 2 diabetes prevention. This study demonstrates that healthy lifestyle health education significantly improves public knowledge and attitudes regarding type 2 diabetes prevention.